The Relationship between Writing Proficiency in English and Metacognitive Awareness of Writing Strategies among EFL University Students - El Madani, El Mehdi; Larouz, Mohammed; Fagroud, Mustapha; Saadallah, Zayneb (Jurnal Arbitrer, 2024)
Scholarly interest in the interplay between metacognition and language learning has notably surged. The expanding corpus of literature uniformly acknowledges the pivotal role that metacognitive knowledge occupies within the framework of language education. Precisely, the metacognitive awareness concerning English as a Foreign Language (EFL) learning strategies empowers learners to supervise, regulate, and optimize their educational endeavors. Metacognitive knowledge encompasses an awareness of one’s linguistic proficiency and the strategies pertinent for its enhancement. Equally, a deficiency in such awareness poses significant impediments to the language learning trajectory. Against this backdrop, the present study probes the nexus between metacognitive knowledge and language learning. the specific objective of the current study is to explore the correlation between EFL college students’ English writing proficiency and their writing metacognitive awareness. In order to reach this goal, a language proficiency test in writing and a Metacognitive Awareness Writing Questionnaire (MAWQ) were employed to collect the data. The participants in the study included 94 university students belonging to the department of English studies at the faculty of Letters and Human Sciences of Meknes and the Higher school for Training and Education of Kenitra. To analyze the collected data, the study made use of various statistical tools, including Simple Linear Regression and Pearson product-moment correlation. The results of the explored connection presented that there is a significant positive relationship between students’ writing performance and their metacognitive awareness of writing, with a ρ -value of 0.793. The results also showed that writing metacognitive awareness could predict 62% of the variability in writing ability. This study has also precipitated a range of implications related to pedagogy and methodology, alongside recommendations for teachers of English, syllabus designers, academic English studies departments, and coming scholarly inquiries.